DAMPAK HARGA KOMODITAS TERHADAP KREDIT BERMASALAH DI INDONESIA - Robby Alexander Sirait (Pusat Kajian Anggaran, 2020)
This paper investigates the impact of commodities price on Non-Performing Loans (NPLs) in Indonesia. This study performed an analysis for the period from 2003 to 2019 by an autoregressive distributed lag (ARDL) model. The outcomes of this research suggest that commodities price influence NPLs significantly. It confirm that the level of NPLs tends to decrease when commodities price rises. Quantitatively, an increase of 1 percent in commodity prices results in a decline of NPLs by 0,862 percentage points in the short run and 4,088 in the long run. The others confirm that the level of NPLs tends to decrease when economic growth rises, exchange rate depreciates, and declining of inflation.